Absorb bioresorbable vascular scaffold vs. everolimus‐eluting metallic stent in small vessel disease: A propensity matched analysis of COMPARE II, RAI, and MAASSTAD‐ABSORB studies. Issue 2 (7th March 2018) - Tarantini, Giuseppe; Masiero, Giulia; Barioli, Alberto; Paradies, Valeria; Vlachojannis, Georgios; Tellaroli, Paola; Cortese, Bernardo; di Palma, Gaetano; Varricchio, Attilio; Ielasi, Alfonso; Loi, Bruno; Steffenino, Giuseppe; et al.
Abstract: Background: Patients with small vessel disease (SVD) are at higher risk of adverse events after PCI compared to non‐SVD patients. In this subset, the use of bioresorbable vascular scaffolds (BVS) has raised particular concern. Objective: We aimed to compare outcomes of Absorb BVS versus a 2nd‐generation metallic everolimus‐eluting stents (EES) in the SVD setting, by pooling patients from three large, prospective studies. Methods: Patients with SVD (reference vessel diameter ≤2.75 mm by QCA) and treated with Absorb BVS were identified in the Italian RAI and the MAASSTAD‐Absorb registries. EES controls were identified in the COMPARE II Trial. We performed a propensity‐score matching using several clinical and angiographic variables. Implantation technique was not object of matching, being device‐specific. Results: Out of 4635 enrolled subjects, 1147 belonged to the SVD population. After matching, we obtained 337 pairs of patients. High clinical and angiographic complexity was found in both groups. Predilation and postdilation rates were significantly higher in BVS patients. No differences were found in terms of the device‐oriented composite end‐point at 1‐year (HR = 1.08, 95%CI 0.5–2.3, P = .8) and 2‐years (HR = 1.28, 95% CI: 0.68–2.43, P = .5). Notwithstanding, higher incidence of definite/probable stent thrombosis was observed in the BVS group at 1 year (HR 4.7, 95%CI 0.8–31.4, P = .08) and 2‐years (HR = 8.34 95%CI 1.1–60.2, P = .04). Conclusion: In this propensity‐matched analysis pooling SVD patients of three large prospective studies, incidence of composite device‐related events was comparable between BVS and EES up to 2 years follow‐up. However, higher rates of stent thrombosis were found in the BVS group.